Role of pharmacists in management of patients with thyroid disorders - Homšek, Ana; Roganović, Maša; Kovačević, Milena; Jovanović, Marija (Archives of Pharmacy, 2022)
Thyroid dysfunction is one of the most prevalent endocrine disorders, especially common in female patients. If patients are not diagnosed in time or adequately treated, the patients’ quality of life can be significantly impaired and additional health problems may occur, considering the key roles of thyroid hormones in the body. Therefore, it is necessary to raise awareness about the importance of recognition of symptoms that may indicate a potential problem with the thyroid gland and help to identify possible causes. For patients who are already being treated with levothyroxine (hypothyroidism), or thiamazole, carbimazole or propylthiouracil (hyperthyroidism), it is necessary to point out the necessity of proper, regular use of the drugs and implementation of accompanying nonpharmacological measures, as well as the potential for the occurrence of adverse reactions and interactions with other drugs or food. A significant role in the mentioned activities should be played by the pharmacist, as the most accessible member of the health team, who can, if necessary, refer the patient to a doctor for diagnosis, monitor the effectiveness and safety of the therapy, and provide appropriate patient counseling.